Security of Deep Groundwater in the Coastal Bengal Basin Revealed by Tracers - D. J. Lapworth; A. Zahid; R. G. Taylor; W. G. Burgess; M. Shamsudduha; K. M. Ahmed; A. Mukherjee; D. C. Gooddy; D. Chatterjee; A. M. MacDonald (Geophysical Research Letters)
Abstract Uncertainty persists regarding the vulnerability of deep groundwater across Asia's megadeltas. In the coastal Bengal Basin aquifer system, shallow groundwater (<100 m) commonly features high salinity or arsenic concentrations, and deep, better‐quality, groundwater supplies drinking water to >80 million people. Here we report new radiocarbon evidence from a network of nine dedicated, multilevel monitoring wells, which indicates residence times of between 103 and 104 years for groundwater at depths >150 m. Modern groundwater detected in some deep abstraction wells using anthropogenic tracers (SF6, CFCs) is attributed to short circuiting of shallow groundwater within wells. Age‐depth profiles and hydrochemical data in monitoring wells confirm the regional resilience of deep groundwater to ingress of shallow contaminated groundwater. Our results are consistent with high regional anisotropy in the aquifer and support continued use of deep groundwater though the potential for leakage of shallow contaminated groundwater in deep abstraction wells requires careful monitoring.